Risk and protective factors of posttraumatic stress disorder among African American women living with HIV. Issue 11 (2nd November 2018) - Andu, Eaden; Wagenaar, Brad H.; Kemp, Chris G.; Nevin, Paul E.; Simoni, Jane M.; Andrasik, Michele; Cohn, Susan E.; French, Audrey L.; Rao, Deepa
ABSTRACT: We sought to examine risk and protective factors for Posttraumatic Stress Disorder (PTSD) among African American women living with HIV. This is a cross-sectional analysis of baseline data from a randomized trial of an HIV stigma reduction intervention. We examined data from two-hundred and thirty-nine African American women living with HIV. We examined whether age, marital status, level of education, internalized HIV-related stigma, and social support as potential protective and risk factors for PTSD symptoms using logistic regression. We analyzed bi-variate associations between each variable and PTSD symptoms, and constructed a multivariate logistic regression model adjusting for all variables. We found 67% reported clinically significant PTSD symptoms at baseline. Our results suggest that age, education, and internalized stigma were found to be associated with PTSD symptoms ( p  < 0.001), with older age and more education as protective factors and stigma as a risk factor for PTSD. Therefore, understanding this relationship may help improve assessment and treatment through evidence- based and trauma-informed strategies.